2019
DOI: 10.1007/s10921-019-0590-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Attenuation in Polycrystalline Materials in 2D

Abstract: Grains in a polycrystalline material, typically a metal, act as scatterers of ultrasonic waves and thus give rise to attenuation of the waves. Grains have anisotropic stiffness properties, typically orthotropic or cubic. A new approach is proposed to calculate attenuation in a 2D setting starting from the scattering by an anisotropic circle in an isotropic surrounding. This problem has recently been solved, giving explicit, simple expressions for the elements of the transition (T) matrix (which gives the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, this subject remains mostly unvisited for strongly scattering polycrystals. A few relevant studies include a recent two-dimensional theory showing applicability to materials of high anisotropy [26] and a theory for strongly scattering materials [27] and the references therein. However, for longitudinal waves, only a small difference is found in [27] from the Stanke and Kino model [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, this subject remains mostly unvisited for strongly scattering polycrystals. A few relevant studies include a recent two-dimensional theory showing applicability to materials of high anisotropy [26] and a theory for strongly scattering materials [27] and the references therein. However, for longitudinal waves, only a small difference is found in [27] from the Stanke and Kino model [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the anisotropy factor, which is a combination of the elastic constants of the material, is representative of the degree of anisotropy and the models lose their accuracy for materials with a high anisotropy factor. On the other hand, Boström & Ruda [28] in two dimensions looked at the polycrystalline materials as a collection of individual grains in which each grain is considered to be surrounded by a matrix with the overall properties of all other grains (which is isotropic for equiaxed and randomly oriented grains). Using the explicit transition matrix for cubic materials presented by Boström [13], explicit expressions for the attenuation are derived for polycrystalline materials with cubic symmetry in two dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The current research found that when ultrasonic vibration acts on the solid medium, the absorption and scattering of ultrasonic by the material will cause the loss of ultrasonic energy, and the ultrasonic intensity gradually attenuates with the increase of propagation distance [21,22]. However, this kind of effect has been not considered in the existing research and analysis.…”
Section: Introductionmentioning
confidence: 99%